If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(0+x)=36
We simplify the equation to the form, which is simple to understand
12(0+x)=36
Reorder the terms in parentheses
+(+12x)=36
Remove unnecessary parentheses
+12x=+36
We move all terms containing x to the left and all other terms to the right.
+12x=+36-0
We simplify left and right side of the equation.
+12x=+36
We divide both sides of the equation by 12 to get x.
x=3
| 0=16-(x-x*0.02*1.19) | | 3+7x=-3+x | | 4(5-4x)=148 | | 25-2y=3y-35 | | 2/3n^2-11=-3 | | 6(10+5x)=360 | | 3n^2-17=3 | | 2x-2=6x+26 | | 15+6z=-15 | | -7c^2=-100 | | 2x+32=12x-45 | | 4(x-1)=12x | | -7n+4a=x | | 4+2(8w+6)= | | 1=12*x^2+11*x | | 16=x-(x*0.02*1.19) | | 2(1-5x)=72 | | 12(3-3x)=60 | | 4b^2-5=-7 | | 2x+6=-18-4 | | 4(2-x)=5(x+1) | | 2(-7x-9)=108 | | 2x+12=3-6 | | 8+5x+4x=44 | | x^4-9y^4=0 | | 1/2x^2-2=6 | | -10b+q=s | | 3(a+4)=-18 | | 7(x+8)=105 | | 5n^2=0 | | 84+12x+48= | | 16=x-x*0.02*1.19 |